보편적 한국음악극 정립을 위한 국립창극단의 역할과 과제: 창극 <청>과 <로미오와 줄리엣>을 중심으로 - 이주영; Lee Joo Young (국제문화예술, 2021)
이 논문의 목적은 보편적 한국음악극 정립을 위한 국립창극단의 역할과 과제를 모색하고자 함이다. 보편적 한국음악극 정립을 위한 국립창극단의 역할과 과제는 다음과 같다. 먼저 공공극장에 소속된 국립창극단은 보편적 한국음악극 정립이라는 예술적 지향점을 설정해야 한다. 가장 중요한 음악에 대한 문제점을 해결하고, 개선해야 한다. 또한 종합예술인 음악극이 제대로 구현되기 위하여 무대예술의 제반 요소를 적극 개발하고, 활용하여야 할 것이다. 무엇보다도 국립창극단의 보편적 한국음악극 정립에 대한 예술적, 정책적 의지가 중요하다. This study aims at looking for roles and missions for National Changgeuk Company of Korea to establish Korean universal music theatres. The roles and missions for National Changgeuk Company of Korea to perform to establish universal Korean musical theatres are as follows; first, as one of the affiliated companies to the public theatre of Korea it definitely has to set up the ultimate goal of composing universal Korean musician theatres. It also should innovate itself by correcting the problems in music which is the most critical. Second, we expect that it should actively develop expanded elements in the theatre art and utilize them to make the musical theatre realized properly as a synthetic art. Last, the most significance to fulfill the company’s roles and missions lies on how strongly willed the company is both artistically and administratively.